Pembuatan Direktori Sanggar Tari di Kota Padang - Rusmaidi, Indah; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThis paper discusses the Making of a Dance Studio Directory in the City of Padang. The purpose of this paper is (a) to describe the making of a directory of dance studios in the city of Padang; (B) describing the transition in creating a directory of dance studios in Padang City; (c) describe the business in making a directory of dance studios in the city of Padang. This research was conducted using descriptive methods by describing the subject or object based on visible facts. Data collected through observation, interviews, and literature study. Based on the research that has been done, it can be concluded, first, the steps in the process of making dance studios in the city of Padang are (a) data collection that collects all information relating to which is not in doubt to be made in the directory; (B) collect all data obtained; (c) Focus on a vision that has been created; (d) making books so that they are easier to produce and making books more directed; (e) determine the subject, the subject used in making the directory is the name of the street, location of each studio; (f) classification or grouping, grouping data that has been collected and adjusted to the subjects that have been determined; (g) directory design that is by making cover designs, and compiling information from directories. Second, the challenges involved in making a dance studio directory in Padang City are as follows: (a) when collecting data the writer had difficulty in finding the dance studio to be addressed. This is because there are some studios that do not have banners or name bars installed. Discusses some problems in finding the studio; (B) some studios that the author visits the owner often go to the studio or the owner is out of town because they have to accompany their students in the race; (c) difficulties in contacting the studio owner. Third, the non-related ones involved in making directories include; (a) the name of the studio; (b) the name of the owner; (c) year of establishment; (d) number of students; (e) hours of practice; (f) address; (g) telephone number; (h) location plan; and (i) studio photos.Keywords: Manufacture, Directory, Dance Studio